KEMAMPUAN BAHASA INDONESIA APARATUR SIPIL NEGARA DALAM KONTEKS PROFESIONALISME BERBAHASA: ANALISIS HASIL UKBI - Kurniawaty, Rahmah; Harjanti, Rina (Jurnal Lingkar Mutu Pendidikan, 2025)
ABSTRACT Proficiency in the Indonesian language is a fundamental competency required of civil servants to support professional communication within governmental institutions. This study aims to analyze the proficiency level of civil servants in using Indonesian in a formal context based on the results of the Indonesian Language Proficiency Test (UKBI). This research employed a quantitative descriptive method with 57 participants from the Educational Quality Assurance Agency (BPMP) of DKI Jakarta Province. The data were obtained from official UKBI results and analyzed using descriptive statistics based on seven levels of language proficiency: Distinguished, Superior, Advanced, Intermediate, Developing, Novice, and Limited. The findings revealed that none of the participants reached the "Distinguished" level, while 21.05% were categorized as "Superior", 12.28% as "Advanced", and 22.81% as "Intermediate". Meanwhile, 24.56% of participants were categorized as having low proficiency levels (Developing–Limited), and 19.30% did not receive a score due to test incompletion. These results indicate significant disparities in Indonesian language proficiency among civil servants. The study suggests that systematic and sustainable language development programs based on UKBI results are needed to strengthen linguistic competence as part of civil service professionalism. The implications of this study also highlight the importance of implementing national language policies in government institutions as mandated by Presidential Regulation Number 63 of 2019 concerning the Use of Indonesian.